Sexism and the Australian voter: how sexist attitudes influenced vote choice in the 2019 federal election. Issue 3 (3rd July 2021) - Beauregard, Katrine
ABSTRACT: While attitudes toward women and gender equality are increasingly salient in Australian politics, little is known about how sexist attitudes shape political behaviour. Using the Australian Election Study, I assess the extent hostile sexism is present among Australian citizens and influenced vote choice in the 2019 Federal election. First, I find that women are less likely than men to hold hostile sexist attitudes, but gender differences vary by party identification. Second, I show that hostile sexism is not significantly related to the likelihood of voting for the Labor or Liberal parties. Hostile sexist attitudes, however, significantly increase the likelihood of voting for the National party and significantly decrease the likelihood of voting for the Greens. Finally, I find no gender difference in the role of hostile sexism in explaining vote choice.